Indication of The Abstract and Augmented Tri Verbs in Surat Al-Moulk (Journal of the College of Education for Women, 2019)
The subject of indication is one of many subjects that the Arabic language interest in and we decide that this research which we called (Indication of the abstract and Augmented Tri verbs) in one of Al-Quran Suras which is Al-moulk to dive in the secrets and knowledge of its meanings and knowledge of its structure in terms of abstraction and increase, And the investigation of our ancient scholars of linguistics and interpreters in its meanings. The verbss were classified according to the structure in which they were presented. The research includes two sections followed by the conclusion of the research, sources and its references. The first section (the indication of the abstract Tri verbs) in the sura is divided into four branches in which a group of actions carried multiple connotations, and the second topic was about the Augmented Tri verbs included two types of verbs the first: the Tri verbs, which are augmented by one letter, the other which are augmented by two letters.Among the results reached is the diversity of verbs in the sura between the abstract and Augmented Tri verbs by one letter and two letters, and the absence of Quadrant verbs, and Augmented verb gave more meaning than the abstract verb, and that is because the increase in letters leads to an increase in meaning.as we have observed the accuracy of the use of the Koran language vocabulary commensurate with the meaning of words and bringing the meaning to the listener as we have reached a difference in the significance of the actions of scientists through the Comparison between two sets the language and the interpretation books. We collect most views that have been said in the Indication of these verbs.